An integrated cellular and molecular model of gastric neuroendocrine cancer evolution highlights therapeutic targets - Griger, Joscha; Widholz, Sebastian A.; Jesinghaus, Moritz; de Andrade Krätzig, Niklas; Lange, Sebastian; Engleitner, Thomas; Montero, Juan José; Zhigalova, Ekaterina; Öllinger, Rupert; Suresh, Veveeyan; Winkler, Wiebke; Lier, Svenja; et al. (Cancer cell, 2023)
Gastric neuroendocrine carcinomas (G-NEC) are aggressive malignancies with poorly understood biology and a lack of disease models. Here, we use genome sequencing to characterize the genomic landscapes of human G-NEC and its histologic variants. We identify global and subtype-specific alterations and expose hitherto unappreciated gains of MYC family members in a large part of cases. Genetic engineering and lineage tracing in mice delineate a model of G-NEC evolution, which defines MYC as a critical driver and positions the cancer cell of origin to the neuroendocrine compartment. MYC-driven tumors have pronounced metastatic competence and display defined signaling addictions, as revealed by large-scale genetic and pharmacologic screening of cell lines and organoid resources. We create global maps of G-NEC dependencies, highlight critical vulnerabilities, and validate therapeutic targets, including candidates for clinical drug repurposing. Our study gives comprehensive insights into G-NEC biology.